Upaya Penyelesaian Pernikahan Beda Agama: Analisis Istidlal Fakhruddin ar-Razi Dalam Kitab al-Mahshul Fi Ilmi Ushul - Muhtolib, Muhtolib; Muhsin, Muhsin (Tasyri' : Journal of Islamic Law, 2024)
Interfaith marriage is a classic problem that is always interesting to discuss because the legal products found in this problem are contradictory. The purpose of writing this article is to describe the method of tafsir ahkam Fakhr al-Din Ar-Razi in al-Mahshul Fi Ilmi Ushul al-Fiqh, to solve the problem of interfaith marriage by using the istidlal method. The approach used in this writing is a descriptive analysis approach, which is an approach used to collect data and information with various materials found in libraries, such as books and articles. The conclusion of this article shows that the effort to solve religious marriage when viewed with istidlal fakhruddin ar-Razi in the book al-Mahshul fi Ilm al-Ushul by using the concept of permissible and the concept of Takhsis al-Maqtu bi Al-Maqtu' (Takhsis dalil qath'i with dalil qath'i) between QS. al-Baqarah [2]: 221 ditakhsis with QS. al-Maidah[5]: 5, then it is permissible on condition that he is an Ahl Kitab. As for Ahl Kitab in the disclosure of the Qur'an da, Jews and Christians as the obvious Ahl al-Kitab. But those who mention other religious groups, namely the Magi and Shabi'in, let alone Buddhists, Hindus and Khong Hucu are not part of Ahl al Kitab, or do not belong to the Ahl al-Kitab community at all,